2020
DOI: 10.1002/cssc.201903072
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of a Hybrid Zn/V2O5 Rechargeable Battery with a Binary Li+/Zn2+ Aqueous Electrolyte

Abstract: Low‐cost, easily processable, and environmentally friendly rechargeable aqueous zinc batteries have great potential for large‐scale energy storage, which justifies their receiving extensive attention in recent years. An original concept based on the use of a binary Li+/Zn2+ aqueous electrolyte is described herein for the case of the Zn/V2O5 system. In this hybrid, the positive side involves mainly the Li+ insertion/deinsertion reaction of V2O5, whereas the negative electrode operates according to zinc dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
(88 reference statements)
1
16
0
Order By: Relevance
“…[ 130 ] It was demonstrated that during discharge/charge of Zn/V 2 O 5 hybrid‐ion battery, a reversible coinsertion/extraction of Li + and Zn 2+ ions into/from the interlayer of V 2 O 5 structure occurred as confirmed by spectroscopy analysis. [ 130 ] Similarly, Batyrbekuly et al [ 131 ] investigated Zn//3 m Li 2 SO 4 + 4 m ZnSO 4 //V 2 O 5 hybrid‐ion battery and demonstrated that this battery involves mainly the insertion/extraction of Li + ions in layered V 2 O 5 and dissolution/precipitation of zinc in the negative electrode. This battery delivered reversible specific capacities of 136 and 125 mAh g −1 at 15 mA g −1 (C/20) and 60 mA g −1 (C/5), respectively.…”
Section: Electrolyte Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 130 ] It was demonstrated that during discharge/charge of Zn/V 2 O 5 hybrid‐ion battery, a reversible coinsertion/extraction of Li + and Zn 2+ ions into/from the interlayer of V 2 O 5 structure occurred as confirmed by spectroscopy analysis. [ 130 ] Similarly, Batyrbekuly et al [ 131 ] investigated Zn//3 m Li 2 SO 4 + 4 m ZnSO 4 //V 2 O 5 hybrid‐ion battery and demonstrated that this battery involves mainly the insertion/extraction of Li + ions in layered V 2 O 5 and dissolution/precipitation of zinc in the negative electrode. This battery delivered reversible specific capacities of 136 and 125 mAh g −1 at 15 mA g −1 (C/20) and 60 mA g −1 (C/5), respectively.…”
Section: Electrolyte Modificationsmentioning
confidence: 99%
“…In a similar manner, hybrid‐ion battery (Zn/V 2 O 5 ) was investigated by Batyrbekuly et al with their original concept of binary Li + /Zn 2+ electrolytes. [ 131 ] The binary electrolyte consists of Li 2 SO 4 and ZnSO 4 , which fully dissociates into their respective ion compositions. The unique mechanism of this hybrid ZIB involves the Li + insertion/extraction in the positive side, whereas Zn dissolution/precipitation occurs in the other (negative).…”
Section: Electrolyte Modificationsmentioning
confidence: 99%
“…Interestingly, in addition to the co‐insertion of Zn 2+ /H + ions, the employ of mixed electrolyte can achieve the co‐insertion of bimetal ions. For example, Batyrbekuly et al assembled a Zn/V 2 O 5 battery with a mixed electrolyte of 3 m Li 2 SO 4 and 4 m ZnSO 4 , [ 72 ] thereby realizing the co‐insertion of Zn 2+ /Li + . The Zn/V 2 O 5 hybrid system has high structural stability and rate performance.…”
Section: Electrochemical Insertion Mechanismmentioning
confidence: 99%
“…We newly applied this concept of rechargeable aqueous hybrid batteries, using the conventional pristine α-V2O5 oxide as cathode material and Zn as anode in 2.5M Li2SO4 + 3.5M ZnSO4 (pH = 4) binary electrolyte with a special emphasis on the structural mechanism involved upon discharge/charge process in the 1.6 V-0.8 V potential range (corresponding to the transfer of one-electron) [37]. The Zn||2.5M…”
Section: Introductionmentioning
confidence: 99%